2022
DOI: 10.3390/biomedicines10081795
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Induces H2O2-Dependent Apoptosis and Ferroptosis in Human Cervical Cancer

Abstract: Sanguinarine (SNG) is a benzophenanthridine alkaloid isolated mainly from Sanguinaria canadensis, Chelidonium majus, and Macleaya cordata. SNG is considered an antineoplastic agent based on its cytotoxic activity against various tumors. However, the exact molecular mechanism through which SNG mediates this activity has not been elucidated. Here, we report that SNG induces death in human cervical cancer (HeLa) cells through activation of two interdependent cell death pathways—apoptosis and ferroptosis. SNG-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Sanguinaria canadensis is the major source of sanguinarine, a quaternary benzophenanthridine alkaloid with anticancer effects (Galadari et al, 2017 ). Very recently, sanguinarine was shown to induce apoptosis and ferroptosis in human cervical cancer (HeLa) cells (Alakkal et al, 2022 ). Both regulated forms of cell death were evoked through sanguinarine-dependent ROS production, especially H 2 O 2 .…”
Section: Natural Compounds As Ferroptosis Inducersmentioning
confidence: 99%
“…Sanguinaria canadensis is the major source of sanguinarine, a quaternary benzophenanthridine alkaloid with anticancer effects (Galadari et al, 2017 ). Very recently, sanguinarine was shown to induce apoptosis and ferroptosis in human cervical cancer (HeLa) cells (Alakkal et al, 2022 ). Both regulated forms of cell death were evoked through sanguinarine-dependent ROS production, especially H 2 O 2 .…”
Section: Natural Compounds As Ferroptosis Inducersmentioning
confidence: 99%
“…This study suggests that OA may be a potential anticancer drug for cervical cancer. According to research on Sanguinarine (SNG) by Alakkal et al [56], SNG caused ferroptosis through SL7A11 and apoptosis through caspase-3 in human cervical carcinoma. A second death mechanism was likewise blocked by the administration of an RCD inhibitor [56].…”
Section: Ferroptosis and Cervical Cancermentioning
confidence: 99%
“…According to research on Sanguinarine (SNG) by Alakkal et al [56], SNG caused ferroptosis through SL7A11 and apoptosis through caspase-3 in human cervical carcinoma. A second death mechanism was likewise blocked by the administration of an RCD inhibitor [56]. This raises the question of whether cancer cells' regulation of H 2 O 2 is what leads to medication resistance.…”
Section: Ferroptosis and Cervical Cancermentioning
confidence: 99%
“…Sanguinarine chloride (S.C) is a natural benzophenanthridine alkaloid extracted from various sources, including the roots of Sanguinaria canadensis, seeds of Argemone Mexicana, and the leaves and fruits of Macleaya cordata [ 13 ]. Numerous studies have reported its pharmacological activity in cancer therapy [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%